A Solvent-Free Reaction for Silyl Enol Ethers Synthesis - Morozzi, Chiara; Rosati, Ornelio; Curini, Massimo; Lanari, Daniela (Synlett, 2018)
Silyl enol ethers are extremely useful nucleophilic intermediates for chemical transformations because they are synthetically versatile substrates for a wide range of C–C bond-forming reactions. Here, we present a new, mild, and solvent-free procedure for the synthesis of silyl enol ethers that employs a catalytic amount of solid-supported base and an equimolar amount of N,O-(bistrimethylsilyl)acetamide as a silylating agent.
Keywords: silyl enol ethers; catalyst support; green chemistry; heterogeneous catalysis; solvent-free conditions